Mountain Birdwatch 1.0 - Vermont Center for Ecostudies; J. Daniel Lambert; Julie Hart (Knowledge Network for Biocomplexity)
Mountain Birdwatch 1.0 is a long-term monitoring program for songbirds that breed in highelevation forests of the northeastern United States. Initiated in 2000, Mountain Birdwatch has prepared skilled volunteers to conduct annual surveys along 1-km point-count routes located in Massachusetts, New York, Vermont, New Hampshire, and Maine. Primary emphasis was placed on Bicknell’s Thrush, a montane-fir specialist that breeds only in the Northeastern U.S. and adjacent portions of Canada. Other focal species included Blackpoll Warbler, Swainson’s Thrush, White-throated Sparrow, and Winter Wren. The Vermont Center for Ecostudies launched a new, revised monitoring program- Mountain Birdwatch 2.0- in June of 2010.